1976
DOI: 10.1073/pnas.73.8.2788
|View full text |Cite
|
Sign up to set email alerts
|

Cell recognition in plants: Determinants of the stigma surface and their pollen interactions

Abstract: The interaction between compatible pollen grains and the female stigma of Gladiolus gandavensis has been used as a model system for investigation of cell recognition in plants. The Cells of virtually all eukaryotic organisms possess some capacity to distinguish self from not-self (1). Processes reflecting this recognition capacity have been extensively explored in animal systems (2), but plants have been largely neglected. However, recognition between compatible pollen and the female stigma in plants provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(55 citation statements)
references
References 17 publications
3
52
0
Order By: Relevance
“…Fewer E. nitens pollen tubes were also counted in the E. globulus style. However, this was consistent with the lower in vitro germination of the E. nitens pollen utilised and there is no evidence of stigmatic inhibition of pollen germination or initial penetration of the style (Knox et al 1976;Stettler et al 1980). Two distinct, although not mutually exclusive, groups of mechanisms (de Nettancourt 1984) have been proposed to account for interspecific incompatibility (sensu de Nettancourt 1977, p. 141).…”
Section: Discussionmentioning
confidence: 50%
“…Fewer E. nitens pollen tubes were also counted in the E. globulus style. However, this was consistent with the lower in vitro germination of the E. nitens pollen utilised and there is no evidence of stigmatic inhibition of pollen germination or initial penetration of the style (Knox et al 1976;Stettler et al 1980). Two distinct, although not mutually exclusive, groups of mechanisms (de Nettancourt 1984) have been proposed to account for interspecific incompatibility (sensu de Nettancourt 1977, p. 141).…”
Section: Discussionmentioning
confidence: 50%
“…Recently, it has been revealed that carbohydrates or glycoproteins serve as determinants of the specificity of various systems such as sexual mating of yeast (21), species-specific aggregation of sponge cells (17), and pollination in plants (11). The results in this paper indicated that the spore-agglutinating factor is a glycoprotein, of which the carbohydrate moiety has a role in its agglutinating activity (Table I).…”
Section: Resultsmentioning
confidence: 60%
“…Golynskaya et al (7) found hemagglutinins in Primula stigmata which also effected pollen tube growth. Pretreatment of Gladiolus stigmata with Con A prevented compatible pollen tubes from penetrating (10). There is also considerable evidence that the specificity of host-symbiont interactions is determined by lectin binding (1,3,4,8,15,21).…”
mentioning
confidence: 99%